2018
DOI: 10.7326/m17-2315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Digital Health Intervention on Receipt of Colorectal Cancer Screening in Vulnerable Patients

Abstract: Background Screening for colorectal cancer (CRC) reduces mortality, yet over one-third of age-eligible Americans are unscreened. Objective To examine the effect of a digital health intervention (mPATH-CRC) on rates of CRC screening. Design Randomized clinical trial. Setting Six community-based primary care practices. Participants 450 patients (223 mPATH-CRC, 227 usual care) scheduled for a primary care visit and due for routine CRC screening. Intervention An iPad app that displays a CRC screening dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
89
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 33 publications
(34 reference statements)
0
89
0
2
Order By: Relevance
“…A study examining the impact of combining a decision aid with patient navigation in a diverse, vulnerable patient population did demonstrate a strong impact on screening completion but was unable to separate the effects of the decision aid from patient navigation . A recent study incorporating an iPad‐based CRC decision aid with test‐ordering capability into the office visit demonstrated a doubling of CRC screening completion from 15% to 30% among vulnerable primary care patients who were randomized to the intervention …”
Section: Options For Crc Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…A study examining the impact of combining a decision aid with patient navigation in a diverse, vulnerable patient population did demonstrate a strong impact on screening completion but was unable to separate the effects of the decision aid from patient navigation . A recent study incorporating an iPad‐based CRC decision aid with test‐ordering capability into the office visit demonstrated a doubling of CRC screening completion from 15% to 30% among vulnerable primary care patients who were randomized to the intervention …”
Section: Options For Crc Screeningmentioning
confidence: 99%
“…179 A recent study incorporating an iPad-based CRC decision aid with test-ordering capability into the office visit demonstrated a doubling of CRC screening completion from 15% to 30% among vulnerable primary care patients who were randomized to the intervention. 180 Nonoffice-based strategies, including "outreach" strategies whereby patients receive invitations to screening via mail, have shown a 5% to 15% increase in adherence rates. Mailed reminders with or without FIT kits/gFOBT cards timed to a scheduled clinic appointment can increase screening.…”
Section: Interventions To Increase Utilization and Adherencementioning
confidence: 99%
“…To date, no review has examined the effectiveness of digital interventions in increasing flu vaccination uptake amongst pregnant women. A recent review has examined interventions that have been used to increase flu vaccination uptake, but current advancements in technology and internet use, and previous demonstrated effectiveness of digital health interventions (22,10,11,12), it is relevant and timely to examine digital flu vaccination interventions.…”
Section: Strengthsmentioning
confidence: 99%
“…A recent randomized trial conducted in community health center practices showed higher rates of CRC screening for patients who received a decision aid and support from a navigator compared with patients who received usual care . Another randomized trial conducted in community‐based primary care settings that serve many low health literacy and low‐income patients showed higher CRC screening rates among patients who received a digital health intervention, including a patient decision aid and self‐referral feature, compared with patients who received usual care …”
mentioning
confidence: 99%
“…10 Another randomized trial conducted in community-based primary care settings that serve many low health literacy and lowincome patients showed higher CRC screening rates among patients who received a digital health intervention, including a patient decision aid and self-referral feature, compared with patients who received usual care. 11 Second, how should the tools be used? We chose to develop decision support interventions that can be used to encourage deliberation between patients and health care providers during the clinical encounter when CRC screening is discussed and tests are ordered.…”
mentioning
confidence: 99%